Analisis Pemetaan Selera Pemirsa Terhadap Atribut Video Penyuluhan Budidaya Padi di Desa Bunga Raya - Lestari, Suci (Politeknik Pertanian Negeri Payakumbuh, 2021)
Video is one of the media that can be used in agricultural extension activities. However, often in practice, the video used is not in accordance with the tastes of farmers and has an impact on the effectiveness of the extension itself. This research was conducted with the aim of identifying the level of farmers' preference for 10 types of videos of rice cultivation extension and analyzing the attributes that affect the attractiveness of rice cultivation video counseling in Bunga Raya Village, Bunga Raya District, Siak Regency. The location selection was done purposively with the consideration that Bunga Raya Village, Bunga Raya District, Siak Regency had an active farmer group and had utilized video media in the extension activities. The sample in this study consisted of 100 farmer panelists to assess the level of preference for the video and 12 expert panelists in attribute assessment. The hedonic test analysis was used to identify the level of farmers' preference for the 10 types of video extension of rice mina cultivation and descriptive test to analyze the attributes that affect the attractiveness of rice video extension education. The results of cluster analysis (AHC) from the hedonic test and Principal Component Analysis (PCA) analysis of the descriptive test are then analyzed using preference mapping techniques. The best video of this study is video number 1 with a respondents' favorite level of 89% and produces a video attribute rating of the most influential namely educational material, understanding material, appropriate material, material to make it easier, story, duration, tested material, gradual material, audio, color, visual, transition, zoom, movie, layout design, back sound, typography, narration, sound effects, video effects, animation, and dialogue. So that preference mapping is very helpful in developing new products by providing a more distinctive visual assessment of hedonic and descriptive data